Investigation Of The Presence Of Antibiotic Residues Influent Of Elazig Municipal Wastewater Treatment Plant - Topal, Murat; Uslu, Gulsad; Sahin, Mehmet; Topal, E. Isil Arslan (Karabuk Univ, 2012)
In this study, it was aimed to determine the presence of antibiotic residues in influents of Elazig Municipal Wastewater Treatment Plant. For this aim, composite sample was taken from the influents of the treatment plant and analyses were done. According to the results of the analyses, macrolides (azitromycin, clarithromycin, erithromycin), beta lactams (aztreonam, cefalosporines (cefamondole, cefepime, cefixime), rifampicine (rifamycin)) and sulfonamide (tetroxoprim) antibiotics were obtained in influents of Elazig Municipal Wastewater Treatment Plant.
Keywords: Antibiotic; treatment; wastewater; pharmaceutical